Intrathecal leptin inhibits expression of the P2X(2/3) receptors and alleviates neuropathic pain induced by chronic constriction sciatic nerve injury - Li, Xin (BioMed Central, 2013)
BACKGROUND: Leptin, an adipocytokine produced mainly by white adipose tissue, has a broad role in the regulation of neuronal functions. Accumulating evidence has revealed that leptin plays an important role in influencing neuropathic pain, shown recently by the finding that chronic administration of leptin induced thermal hyperalgesia and mechanical allodynia in naïve rats. Chronic constriction sciatic nerve injury (CCI) is a well characterized model used for studying neuropathic pain. The present study was designed to investigate whether leptin plays a role in neuropathic pain in rats induced by CCI by examining particular pain behaviors. RESULTS: After sciatic nerve injury in rats, endogenous levels of leptin and leptin receptor (OB-Rb) were increased in a time dependent manner within the ipsilateral dorsal root ganglion (DRG). Intrathecal administration of leptin once daily for 6 days, beginning 7 days after CCI, alleviated neuropathic pain and decreased the expression of IL-6, TNFα, and the P2X(2) and P2X(3) receptors. Attenuation of endogenous OB-Rb in the DRG by intrathecal administration of OB-Rb antisense oligonucleotides did not change thermal hyperalgesia or mechanical allodynia induced by CCI. CONCLUSIONS: Our findings suggest that exogenous leptin can alleviate the chronic neuropathic pain caused by CCI. The leptin effect may be mediated by attenuated expression of IL-6, TNFα, and the P2X(2) and P2X(3) receptors in the DRG of CCI rats.